SAP SuccessFactors Talent a complete guide to configuration, administration, and best practices : performance and goals; Volume 1 - Traynor, Susan; Wellens, Michael A.; Krishnamoorthy, Venki (Apress, 2021)
Take an in-depth look at SAP SuccessFactors talent modules with this complete guide to configuration, administration, and best practices. This two-volume series follows a logical progression of SAP SuccessFactors modules that should be configured to complete a comprehensive talent management solution. The authors walk you through fully functional simple implementations in the primary chapters for each module before diving into advanced topics in subsequent chapters. In volume 1, we start with a brief introduction. The next two chapters jump into the Talent Profile and Job Profile Builder. These chapters lay the structures and data that will be utilized across the remaining chapters which detail each module. The following eight chapters walk you through building, administering, and using a goal plan in the Goal Management module as well as performance forms in the Performance Management module. The book also expands on performance topics with the 360 form and continuous performance management in two additional chapters. We then dive into configuring the calibration tool and how to set up calibration sessions in the next two chapters before providing a brief conclusion. Within each topic, the book touches on the integration points with other modules as well as internationalization. The authors also provide recommendations and insights from real world experience. Having finished the book, you will have an understanding of what comprises a complete SAP SuccessFactors talent management solution and how to configure, administer, and use each module within it. You will: · Develop custom talent profile portlets · Integrate Job Profile Builder with SAP SuccessFactors talent modules · Set up security, group goals, and team goals in goals management with sample XML · Configure and launch performance forms including rating scales and route maps · Configure and administrate the calibration module and its best practices.
Includes index. - Online resource; title from PDF title page (SpringerLink, viewed April 27, 2021)
Keywords: Personnel management -- Computer programs; Employees -- Coaching of -- Computer programs; Personnel; Direction; Logiciels; Personnel management; Computer programs